ANALISIS PENENTUAN WEIGHT PRIORITY MENGGUNAKAN PENDEKATAN GEOMETRIC MEAN DENGAN METODE SUMVECTOR UNTUK PEMILIHAN FASILITASI DI LINGKUNGAN PERUMAHAN (Jurnal Pilar Nusa Mandiri, 2014)
The method used in the development of the Analytic Hierarchical Process (AHP) varies one time, including approaches using geometric averages. This approach uses a technique that is much different because it is done with a Multi-Criteria Analysis approach and its derivatives. In the selection of facilities in residential areas, it is necessary at all levels to measure the priorities of a number of criteria and sub-criteria used. Therefore the geometric mean approach is used as a barometer in the solution approach to determine its priority weights. There are several criteria used to assess the environment for selecting housing facilities that include criteria for benefits, the role of public contributions, the role of local government, and community aspects of these criteria. This criterion will be assessed as the main criterion in the discussion of this paper, which is used as an alternative while the viewing facilities include entertainment facilities, sports facilities, transportation facilities, and shopping facilities. From the discussion, this paper obtained the priority level of the synthesized value as follows: ranking of the first and subsequent decisions including transportation, entertainment facilities, shopping facilities, and final ranked sports facilities, with their respective predicates in the order, were 0.397; 0.273; 0.173; 0.157. The value of this decision is the final synthesis.
Keywords: Analytic Hierarchical Process; GEOMETRIC MEAN; METODE SUMVECTOR